2012
DOI: 10.1089/vbz.2012.0959
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Flaviviruses and Alphaviruses in Livestock and Wildlife in Trinidad

Abstract: Seroprevalence rates of selected arboviruses in animal populations in Trinidad were determined using serum samples collected between 2006 and 2009 from horses (n = 506), cattle (n = 163), sheep (n = 198), goats (n = 82), pigs (n = 184), birds (n = 140), rodents (n = 116), and other vertebrates (n = 23). The sera were screened for antibodies to West Nile virus (WNV), St. Louis encephalitis virus (SLEV), Ilheus virus (ILHV), Bussuquara virus (BSQV), Venezuelan equine encephalitis virus (VEEV), eastern equine enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…However, in contrast to our study, the latter detected antibodies to EEEV, albeit at a low rate (0.6%) (Price, ). In the case of WNV, a recent study demonstrated the presence of WNV reactive antibodies among horses in Trinidad, but all livestock and wildlife (including birds) tested were seronegative (Thompson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to our study, the latter detected antibodies to EEEV, albeit at a low rate (0.6%) (Price, ). In the case of WNV, a recent study demonstrated the presence of WNV reactive antibodies among horses in Trinidad, but all livestock and wildlife (including birds) tested were seronegative (Thompson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The classical HI and MNT methodologies used during this investigation are based on the conventional serologic diagnosis of fl avivirus due to the presence of virus-specifi c antibodies in the serum. Similar serological strategies have been used to detect SLEV in primates 23 , white-tailed deer 19,29 , livestock 11 , mules 19 , and horses 8,10,11,17,18 . The importance of these results lies primarily in the observation of SLEV circulation in a completely new habitat within Brazil, considering that most cases of SLEV have been described within the Amazon region 4,[20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, in a seroepidemiological survey conducted in French Guiana, primates had low antibody titers to SLEV (HI <40) but elevated titers to yellow fever (HI >320), and the authors suggested that that SLEV antibodies identifi ed could have been due to crossreactions with yellow fever virus 23 . Low titers of SLEV were also identifi ed in horses, livestock, and wildlife from the island of Trinidad 11 . However, during this investigation, seropositivity was only identifi ed for SLEV, and negative results were obtained with all other viruses by HI, indicating that there was no crossreaction with any similarly related virus.…”
Section: Neutralization Logarithmic Index Testmentioning
confidence: 99%
“…In Costa Rica, the seroprevalence in two‐toed sloths ( Choloepus spp.) was 11%; in Mexico, the seroprevalence in cattle was 45%, in Trinidad, the seroprevalence in horses was 0.8% for samples taken between 2006 and 2009 (Thompson et al., ) and in bats it was 2.9% (2006–2008) (Thompson et al., ).…”
Section: Assessmentmentioning
confidence: 99%